The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12289-009-0524-7
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of lightweight frame structures by innovative joining by forming processes

Abstract: The majority of the materials used in modern lightweight frame structures are aluminium alloys. But some aluminium alloys, e.g. EN-AW6060, are not or hardly joinable using conventional joining techniques. In this case innovative joining methods like friction stir welding; joining by dieless hydroforming or by electromagnetic compression lead to good joint's quality. Friction stir welding has been widely investigated for joining sheet metal, but joining tubular workpieces creates new challenges in handling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…A large number of techniques is used to make sheet metal parts. In recent years, many aspects of sheet metal forming processes have been widely studied using electromagnetic forming, especially with regard to the behavior of materials under a high strain rate, the possible future applications and numerical modeling of the process, with several works dedicated to these topics [1][2][3][4][5][6][7]. Moreover, a detailed review of numerical simulations in sheet metal forming and potential developments is presented by Tekkaya [8].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of techniques is used to make sheet metal parts. In recent years, many aspects of sheet metal forming processes have been widely studied using electromagnetic forming, especially with regard to the behavior of materials under a high strain rate, the possible future applications and numerical modeling of the process, with several works dedicated to these topics [1][2][3][4][5][6][7]. Moreover, a detailed review of numerical simulations in sheet metal forming and potential developments is presented by Tekkaya [8].…”
Section: Introductionmentioning
confidence: 99%
“…Marré et al investigated the feasibility of friction stir welding tubes by using a self-developed clamping device. It was reported that the macrosection was free of any joint defect, except for an excess weld metal of about 0.2 mm in the center because of the incomplete contact between the tool shoulder and the work pieces [9]. Urso et al published some works on the weldability of aluminum tubes by means of FSW process, and the influence of the welding process on weld quality was investigated, namely feed rate and rotational speed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As a solidstate process, it produces superior as-welded mechanical properties [1], and attracts the increasing attention in manufacturing lightweight components for automotives and aircrafts due to economical and ecological reasons [2][3][4]. Despite various advantages associated with the use of FSW, forming of FSW welds is still challenging due to the limit formability.…”
Section: Introductionmentioning
confidence: 99%
“…The joints are vulnerable to the strain localization in the NZ (nugget zone) due to the material property changes [10] and excess thickness reduction in the weld [2,11], which consequently result in limit formability. Moreover, it is reported that FSW usually leads to the replacement of original homogeneously microstructure with highly heterogeneous distribution, which greatly decrease the elongation of joint during transverse tensile test [12,13].…”
Section: Introductionmentioning
confidence: 99%